Efficacy of exergaming dance and aerobic dance on young adults’ enjoyment, situational motivation, self-efficacy, and steps - Tan, Kai; Autry, Anna Kate; Oginni, John; Tao, Kun; Gao, Zan (Frontiers in Psychology, 2025)
IntroductionThis study explored differences in young adults’ enjoyment, situational motivation, self-efficacy, and physical activity between two content-identical exercise formats: exergaming aerobic dance and traditional aerobic dance.MethodsA total of 40 young adults (20 females; Mage = 20.38) from a Chinese university participated in two separate 12-min dance sessions: (1) a non-stop exergaming aerobic dance using the Xbox 360, Kinect Just Dance and (2) a traditional aerobic dance led by an experienced instructor. Psychological measures of self-efficacy, enjoyment, and situational motivation (including intrinsic motivation, identified regulation, external regulation, and amotivation) were assessed using validated questionnaires after each session. Physical activity levels were measured using a research-grade pedometer to track steps. A repeated-measures MANOVA compared the outcomes between the two dance modalities.ResultsStatistically significant differences were observed between the two dance sessions for the overall model (p < 0.05). Participants reported higher enjoyment during the exergaming dance session compared to the traditional aerobic dance [F (1,39) = 3.59, p = 0.05, η2 = 0.07]. Intrinsic motivation were significantly higher for exergaming dance than for the traditional format [F (1,39) = 3.83, p < 0.05, η2 = 0.09]. However, participants achieved significantly more steps per minute in the traditional aerobic dance compared to the exergaming session [F (1,39) = 39.79, p < 0.01, η2 = 0.51]. No other significant differences were found for the remaining outcomes.DiscussionThese findings suggest that exergaming dance may enhance perceived enjoyment and intrinsic motivation, leading to more time spent on exercise or physical activity, though it results in fewer steps per minute than traditional aerobic dance. These results are practically relevant for promoting long-term physical activity through game-like exercises, as higher enjoyment and motivation play a crucial role in maintaining physical activity.